DETECTION OF NONTUBERCULOUS MYCOBACTERIA (NTM) IN ISOLATES FROM SUSPECTED TUBERCULOSIS USING PCR IS6110 GENE - Andi Nur Asrinawaty; Muh Nasrum Massi; Rizalinda Sjahril (Faculty of Medicine, Hasanuddin University., 2016)
ABSTRACT Introduction: NTM is a group of mycobacterium other than M.tuberculosis complex and M.Leprae, which found in the environment and can be pathogenic. Objectives: This study aim was to detect NTM isolates using PCR on target genes IS 6110. Methods: This study was conducted in Laboratory of Microbiology, Faculty of Medicine, Hasanuddin University and Laboratorium microbiology in Hasanuddin University Hospital. 14 sample isolates of NTM from sputum of suspected tuberculosis patients. The method using PCR IS6110 gene. Results: The results showed that of 14 samples, 8 positive samples with M. tuberculosis and 6 samples negative. Conclusions: IS6110 PCR can be used to detect NTM isolates from sputum of suspected tuberculosis patients. Keywords : NTM, PCR, IS6110, M.tuberculosis